Going solo: How starting solo self-employment affects incomes and well-being - Jonathan Cribb; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2020)
Using a large-scale panel data set, we trace the evolution of incomes and well-being around the entry into 'solo self-employment' - that is, running a business without employees. We find that solo self-employment is used to self-insure against employment shocks: employment rates fall and poverty rates rise in the run-up to entry, and many who fell out of employment report being dismissed or made redundant from their previous job. However, their average earnings do not fully recover within three years of entry. For those who move into solo self-employment directly from employee jobs, for whom this transition is more likely to have been voluntary, earnings remain lower and poverty rates higher for at least two years after entry. Despite the effect on incomes, becoming solo self-employed is associated with improvements in well-being across a number of measures. We see a large and sustained rise in job satisfaction, even among groups who are likely to be using solo self-employment to self-insure. Comparing entries into solo self-employment with entries into or moves between employee jobs, we find that well-being trajectories are remarkably similar despite significantly lower earnings in solo selfemployment. This suggests that there may be intangible benefits that compensate for lower earnings, that (on average) apply even to those who are 'pushed' into solo self-employment.
Keywords: J31; J32; J65; J81; I31; 330; Self-employment; atypical work; job satisfaction; well-being